1985
DOI: 10.1007/bf01533257
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual support for caregivers of dementia patients

Abstract: Dementia is considered the "major psychiatric disorder of old age" and affects over 4 million people in the United States. As Alzheimer's disease and other dementias progress, the patient can become increasingly dependent on the family for care. This dependency can place the caregiver in a role that is both difficult and demanding. In this study coping strategies used by family caregivers of dementia patients and caregivers' sense of burden were assessed. Burden scores were significantly correlated with spirit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…The present study supports the voluminous literature on the beneficial role of perceived spiritual support, one that derives from an individual's faith in coping (Dohrenwend & Dohrenwend, 1981; Levin, 1994; Mackenzie et al, 2000; Maton, 1989; Pargament, 1997; Spilka & Schmidt, 1983; Wright et al, 1985). Based on a “prayer communion” hypothesis (James, (1901/1902/1958), our findings also reinforce the theoretical assumption that links faith and optimistic expectations in positive psychology and faith research (Hood et al, 1996; Levin, 2001; Peterson, 2000).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The present study supports the voluminous literature on the beneficial role of perceived spiritual support, one that derives from an individual's faith in coping (Dohrenwend & Dohrenwend, 1981; Levin, 1994; Mackenzie et al, 2000; Maton, 1989; Pargament, 1997; Spilka & Schmidt, 1983; Wright et al, 1985). Based on a “prayer communion” hypothesis (James, (1901/1902/1958), our findings also reinforce the theoretical assumption that links faith and optimistic expectations in positive psychology and faith research (Hood et al, 1996; Levin, 2001; Peterson, 2000).…”
Section: Discussionsupporting
confidence: 85%
“…We speculated that positive attitudes and spiritual support may serve as mediators between faith and the outcomes of well‐being. To date, this proposed pathway remains largely unexplored empirically, despite numerous assertions about the stress‐buffering effect of a perceived meaningful relationship with a higher power (Dohrenwend & Dohrenwend, 1981; Levin, 1994; Mackenzie et al, 2000; Maton, 1989; Wright, Pratt, & Schmall, 1985). The hypothesized associations among our constructs, however, have further theoretical and empirical justification than just a “prayer communion” hypothesis and the evident protection of optimism.…”
Section: Mediation Of Positive Attitudes and Spiritual Support Betweementioning
confidence: 99%
“…The relationship between spiritual support and decreased distress has been empirically supported in studies of Christian church members (Pargament, 1990), parents mourning the death of a child (Maton, 1989), adults with cancer (Yates, Chalmer, St. James, Follansbee, & McKegney, 1981), caregivers of family members with dementia (Wright, Pratt, & Schmall, 1985), hospice workers (Schneider & Kastenbaum, 1993), and among community elders (Idler, 1987;Koenig, George, & Siegler, 1988), and elders undergoing major surgery (Harris, et al, 1995;Oxman, Freeman, & Manheimer, 1995;Shrimali & Broota, 1987). Oxman, Freeman, and Manheimer (1995) interviewed 232 openheart surgery patients before surgery, and one and six months after surgery.…”
Section: The Relationships Between Religious Coping Health and Wellmentioning
confidence: 95%
“…Furthermore, among a sample of 40 adult heart transplant patients interviewed over one year post-transplant, those who reported higher general levels of activity within their congregation went on to have significantly higher self-esteem levels by the final interview (Harris, Dew, Lee, Amaya, Buches, Reetz, & Coleman, 1995). Finally, Wright, Pratt, and Schmall (1985) found that, among caregivers of individuals with Alzheimer's disease, spiritual support was associated with a decreased experience of burden.…”
Section: The Relationships Between Religious Coping Health and Wellmentioning
confidence: 97%
“…FAITH A significant body of literature is available on the beneficial role of perceived spiritual support that one that derives from using faith to cope in a variety of circumstances (Levin 1994;Mackenzie, Rajagopal, Meibohm, and Lavizzo-Mourey 2000;Maton 1989;Pargament 1997;Spilka and Schmidt 1983;Wright, Pratt, and Schmall 1985). After the September 11th terrorist attacks, it was found that Americans with varied backgrounds turned to prayer for coping and faith-based virtues surged among Americans, whereas secular character strengths did not (Peterson and Seligman 2003).…”
Section: Information Seekingmentioning
confidence: 96%